2012
DOI: 10.1371/journal.pone.0045440
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Restricts Toxoplasma gondii Development in Murine Skeletal Muscle Cells via Nitric Oxide Production and Immunity-Related GTPases

Abstract: The apicomplexan parasite Toxoplasma gondii is regularly transmitted to humans via the ingestion of contaminated meat products from chronically infected livestock. This route of transmission requires intracellular development and long-term survival of the parasite within muscle tissue. In this study, we determined the cell-autonomous immunity of mature primary embryonic or C2C12 skeletal muscle cells (SkMCs) to infection with T. gondii. Non-activated SkMCs and control fibroblasts sustained parasite replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…S7. In mice, astrocytes can use IRGs to restrict T. gondii infection; mMSCs use iNOS to produce NO; and skeletal muscle cells use both mechanisms (27). The mGBPs may also critically contribute to fighting T. gondii replication in vivo (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S7. In mice, astrocytes can use IRGs to restrict T. gondii infection; mMSCs use iNOS to produce NO; and skeletal muscle cells use both mechanisms (27). The mGBPs may also critically contribute to fighting T. gondii replication in vivo (18).…”
Section: Discussionmentioning
confidence: 99%
“…The iNOS-mediated production of NO is a well-known molecular effector against pathogens in the innate immune responses of various animals, including mMSCs (9) and skeletal muscle cells (27), and also in vivo (15,30,31). However, a previous study reported that iNOS protein expression was not detectable in human MSCs (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasites that escape this response then disseminate throughout the host and IFNγ production by innate and adaptive cells is required for control of parasite growth (19). The mechanisms by which IFNγ operate to limit tachyzoite proliferation include induction of immunity-related GTPases and inducible nitric oxide synthase in a number of host cell types including M1 (20, 21). Immune pressure induces the transition of parasite to slow growing tissue cysts (bradyzoites) that resides in the skeletal muscle and central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the status of the hosts' immune function is a critical determinant for the outcome of T. gondii infection [17, 18]. Stress is one important factor affecting the immune function of animals.…”
Section: Introductionmentioning
confidence: 99%